STRUKTUR PASAR DALAM PERSPEKTIF EKONOMI ISLAM DAN IMPLIKASINYA TERHADAP EKONOMI MODERN : STUDI LITERATUR - Nayla Hidayatul Mawadat; Siti Warsini Ningsih; Amalia Nuril Hidayati (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study identifies the characteristics of market structures in Islamic economics that are different from conventional economics, especially in terms of the prohibition of usury, gharar, monopoly, and the emphasis on social justice through the principle of hisbah. This study also discusses the differences between Islamic market structures and modern economic markets that tend to ignore social balance. The implications of the principles of Islamic market structures provide important contributions to designing fair and sustainable public policies. This research method uses a descriptive qualitative approach through literature studies that include data collection and analysis from various sources such as scientific journals, Islamic economics books, relevant scientific publications. An in-depth analysis of the thoughts of experts and previous studies allows for the development of stronger theoretical arguments, a deeper understanding of the principles of Islamic market economics, and their comparison with conventional economics.